QUR'ANIC INSPIRATION FOR LEARNING LANGUAGE: A COMPARATIVE STUDY - Dariyanto Dariyanto; Haris Hamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Language learning is a crucial phase in human cognitive development, as described in the revelations of the Qur'an. Verse QS. Al-Baqarah/ 2:31 illustrates how Allah SWT gave Prophet Adam As knowledge of the names (of objects) as a form of scientific initiation, which provides deep inspiration regarding a holistic and direct approach to language learning. This study aims to compare the inspirational approach of this verse with the Direct Method (DM) in modern language teaching, which prioritizes the direct use of the target language without translation, through verbal, visual, and real-life context interactions. The research methodology is qualitative with a hermeneutic approach, which involves the interpretation of the Qur'an (based on sources such as Tafsir Ibn Kathir and Tafsir al-Mishbah) and pedagogical literature analysis. The comparison focuses on key learning elements, such as the rejection of rigid and traditional grammatical methods, and an emphasis on direct experience and natural repetition to build language competence. The results of the study reveal similarities and differences between the two approaches: both emphasize direct experience and authentic interaction, but inspiration from the Qur'an enriches the Direct Method (DM) with a spiritual dimension, in which the learning process is seen as a divine mandate that triggers intrinsic motivation. The practical implications include the integration of Qur’an values.